Integrating Artificial Intelligence in Islamic Religious Education: Pedagogical Opportunities, Ethical Challenges, and Teacher Competencies - Aji Setiaji (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The rapid integration of Artificial Intelligence (AI) in education presents unprecedented pedagogical opportunities and profound ethical dilemmas, particularly within Islamic Religious Education (PAI) for Generation Z. This study aims to explore AI's substantive opportunities, algorithmic ethical challenges, and the requisite teacher competencies needed to navigate this disruption. Methods: A qualitative Systematic Literature Review (SLR) was conducted adhering to PRISMA guidelines. Scientific documents published between 2019 and 2024, indexed in Scopus, Web of Science, and SINTA databases, were analyzed using thematic synthesis. Findings indicate that AI offers significant pedagogical opportunities, including adaptive learning personalization, enhanced student engagement through interactive conversational agents, and data-driven holistic evaluation. Conversely, crucial ethical challenges emerge, primarily concerning student data privacy, algorithmic biases reflecting secular paradigms, pedagogical transparency, and the potential degradation of spiritual authenticity due to AI hallucinations. To mitigate these risks, PAI teachers must fundamentally elevate their technical, digital-pedagogical, and Islamic-ethical competencies. The study proposes a comprehensive ethical framework grounded in the Islamic worldview (Tawhid, Khalifah, Ta'dīb) and Maqasid al-Shariah. Policy recommendations emphasize restructuring the national curriculum to include digital ethics, modernizing teacher training, establishing strict sectoral guidelines, and transforming evaluation instruments to be AI-proof. Ethical AI integration does not replace teachers but repositions them as essential spiritual architects.